Crime lab 101 : experimenting with crime detection - Gardner, Robert, 1929- (New York : Walker, 1992)
Introduces techniques of criminal investigation, including fingerprint and voice pattern examination, handwriting analysis, and ballistics, and discusses the development of forensic science.
Includes bibliographical references (p. [119]-120) and index.
Appraisal-Science Books for Young People.
School Library Journal.
Wilson's Junior High School.
7-9
Young Adult
Keywords: Criminal investigation -- Juvenile literature; Criminal investigation; Criminal investigation